An exploratory study on programming skill competency among ICT students in Malaysia / Normasniza Mat Ghani - Mat Ghani, Normasniza (2014)
This paper presents the perceptions of employers and educators concerning the programming skills, knowledge and characteristics which help undergraduates to be more marketable. And, also gauge the understanding of programming skills and related issues among CS undergraduate students. The results of this survey indicate that undergraduates are agreed with suggestions given which they want many improvements in teaching and learning programming. By asking the perception from employers and education regarding on how to produce a quality graduates and be more marketable, it is possible for educators to enhance the teaching and learning to meet expectations and to make curriculum changes or adjustments to address these problems. While the study does not suggest that any dominant attributes are related to success in programming, there are some interesting outcomes which will have implications for teaching and learning.